Pengolahan Citra Obyek dari Balik Penghambur dengan Metoda Optik (Tapis Ruang) dan Metoda Digital (âOr Minimumâ) - E. Juliastuti; A. Handojo; Bambang S. P. Abednego; Moedji Raharto (Institute for Research and Community Services (LPPM) ITB, 2005)
In this paper, optical and digital methods are combined to improve the quality of the image obtained through a scattering medium. The optical method, using simply an imaging positive lens and a small circular spatial filter, succeded in the first stage to form an observable image.Two criteria were adopted to evaluate the quality of the image in the optical method. The first is Peak Signal-to-Noise Ratio (PSNR), the second is the correlation coefficient between the original image and the processed scattered image. It was found that PSNR decreased at a larger diameter of the spatial filter. The optimum correlation coefficient (0.368) was found at a filter diameter of 1.6 mm.Next, the digital image processing was conducted using the assumption that the scattering medium always moved randomly. Involving different diameters of the spatial filter, the image was recorded with a CCD camera connected to a computer. For each diameter, the image was recorded many times, each time with a different position of the scattering medium. The images were then processed with the so-called âOr Minimumâ and the averaging method.In the âOr Minimumâ method, the gray level of the same pixel position of all images was compared to find its minimum value. The ensemble of pixels having the minimum gray level constitutes a new image. In the averaging method, the average gray level in each pixel position was computed from a number of images.It appeared that the âOr Minimumâ method yielded the best improvement in PSNR (the largest being 4.00 dB) compared to the averaging method (1.04 dB). The improvement of the correlation coefficient was up to 0.072 in the âOr Minimumâ method and 0.05 in the averaging method.